Development of an Indirect ELISA and Dot-Blot Assay for Serological Detection of Rice Tungro Disease - Henry Sum, Magdline Sia; Yee, Siew Fung; Eng, Lily; Poili, Evenni; Landin, Julia (Hindawi, 2017)
Rice tungro disease (RTD) is one of the most destructive diseases of rice in South and Southeast Asia. RTD is routinely detected based on visual observation of the plant. However, it is not always easy to identify the disease in the field as it is often confused with other diseases or physiological disorders. Here we report the development of two serological based assays for ease of detection of RTD. In this study we had developed and optimized an indirect ELISA and dot-blot assay for detection of RTD. The efficiency of both assays was evaluated by comparing the specificity and sensitivity of the assays to PCR assay using established primer sets.The indirect ELISA showed 97.5% and 96.6%, while the dot-blot assay showed 97.5% and 86.4% sensitivity and specificity, respectively, when compared to established PCR method. The high sensitivity and specificity of the two assays merit the use of both assays as alternative methods to diagnose RTD. Furthermore, the dot-blot assay is a simple, robust, and rapid diagnostic assay that is suitable for field test for it does not require any specialized equipment.This is a great advantage for diagnosing RTD in paddy fields, especially in the rural areas.